Implementation Of Legal Protection On Royalty Management Of Government Regulation Number 56 Of 2021 (Faculty of Law, Universitas Negeri Semarang, 2021)
Abstracts This article examines Government Regulation Number 56 of 2021 concerning the management of royalties on song/music copyrights. This writing uses a normative juridical approach. This normative juridical approach is employed based on the statutes of black letter law and the conceptual method. The result of the study found that royalty management is carried out by LMKN depend on integrated data in the data/song center. Every public at large can enjoy songs/music commercially to public services by applying for a license agreement to the copyright holder or related rights through LMKN intermediaries.The Directorate General of Intellectual Property Rights is obliged to disseminate this regulation and build a data center to control the database of the song/music and ownership of copyright. Therefore, it requires cooperation between the Directorate General of Intellectual Property Rights, LMKN, creators/owners of related rights, and the general public who enjoy commercial songs/music. After the socialization, a strict penalty will be imposed on those who violate or deny paying the stipulated royalty in Government Regulation Number 56 of 2021. Keywords: Copyright;Legal Protection; Royalty Management; Music/Song